2017
DOI: 10.1186/s13013-017-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

Do the SRS-22 self-image and mental health domain scores reflect the degree of asymmetry of the back in adolescent idiopathic scoliosis?

Abstract: BackgroundPatient-reported outcomes are becoming increasingly recognised in the management of patients with adolescent idiopathic scoliosis (AIS). Integrated Shape Imaging System 2 (ISIS2) surface topography is a validated tool to assess AIS. Previous studies have failed to demonstrate strong correlations between AIS and patient-reported outcomes highlighting the need for additional objective surface parameters to define the deformities associated with AIS. The aim of this study was to examine whether the Scol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…In light of increasing emphasis and recognition of patient-reported outcomes, quantitative HRQoL measures that explore the psychosocial impacts of AIS have become mainstay in evaluating treatment success amongst clinicians [177]. Our analysis corroborates this, showing approximately equal radiographic and quantitative HRQoL measures amongst the different schools of treatment (Table 3).…”
Section: Evaluating the Clinical Utility Of Quantitative Hrqol Outcom...supporting
confidence: 76%
“…In light of increasing emphasis and recognition of patient-reported outcomes, quantitative HRQoL measures that explore the psychosocial impacts of AIS have become mainstay in evaluating treatment success amongst clinicians [177]. Our analysis corroborates this, showing approximately equal radiographic and quantitative HRQoL measures amongst the different schools of treatment (Table 3).…”
Section: Evaluating the Clinical Utility Of Quantitative Hrqol Outcom...supporting
confidence: 76%
“…The impact of posterior spinal instrumented fusion on quality of life has been extensively studied. Moreover, the correlation between domain scores and variables such as sex and follow-up years after surgery is also reported in the literature [16][17][18][19]. In our study, we also looked at the correlation between mean scores of each domain and age at the time of surgery.…”
Section: Discussionmentioning
confidence: 60%
“…Wong et al [ 38 ] suggested an association between back pain and depressive mood in patients with AIS. Several studies indicated that the degree of curve was related to self-image [ 2 , 25 ]; however, studies showing the opposite result also exist [ 5 , 34 ]. In many studies, surgery was related to improvement of self-image and quality of life [ 7 , 10 , 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%